O papel da integração regional para o Brasil: universalismo, soberania e percepção das elites - Vigevani, Tullo [UNESP]; Favaron, Gustavo de Mauro [UNESP]; Ramanzini Júnior, Haroldo; Correia, Rodrigo Alves [UNESP] (Instituto Brasileiro de Relações Internacionais, 2008)
O objetivo deste trabalho é analisar o significado do Mercosul para a política exterior do Brasil. Para isso, discutiremos as percepções das elites brasileiras em relação ao processo de integração regional. A defesa do princípio da intergovernamentalidade está ligada à concepção do lugar do Mercosul nas relações internacionais do país. A grande valorização de princípios como o do universalismo e o de soberania acaba afetando o aprofundamento da integração. A hipótese deste trabalho é que a estrutura do Mercosul seria condizente com as percepções de parte das elites brasileiras. Argumentaremos que a estrutura atual é insuficiente para garantir a dinâmica da integração.

The aim of this article is to analyse the role of Mercosur for the Brazilian foreign policy. We will discuss the perception of the Brazilian elites concerning the regional integration process. The defense of the principle of intergovernmentalism is related to the conception of Mercosur's place in the set of Brazilian international relations. The huge valuation of some principles, as universalism and sovereignty, ends up by affecting the deepening of integration. The hypothesis of this paper is that the Mercosur structure would be related with part of Brazilian elite's perceptions. Our argument is that the current structure is insufficient to guarantee the dynamics of the integration.
The role of regional integration for Brazil: universalism, sovereignty, autonomy and elites' perception
Keywords: Autonomia; Universalismo; Política Externa Brasileira; Mercosul; Autonomy; Universalism; Brazilian Foreign Policy; Mercosur